Leucaena (leucaena leucocephala) y maní forrajero (arachis pintoy) henificados en engorde de conejos neozelandes (oryctolagus cuniculus) sexados. - Yepez Cedeño, Daniel Fernando (2012)
This research was carried out at the "Las Mercedes" owned by Mrs. Santa Elizondo, located in the province of Los Ríos Region Buena Fe, to the enclosure via Joy of Congo, whose coordinates are: 0.89 ° 55 ° South Latitude and 0.79 ° 49.03 ° W. to a height of 73 meters. Consisted of 48 cages, each with 2 rabbits, giving a total of 96 experimental units. For this investigation we used a complete randomized design with a factorial arrangement of 2 x 2 x 4, with the factor A food combination or diet, factor B the sex of the animals and the factor C concentrations. For comparison of treatment means used the Tukey test at 95% probability. The following variables were measured: Initial weight, weight gain in 10 days, feed intake, feed conversion, carcass yield (%), cost / benefit ratio. Below are the treatments under study: T1 Maní forrajero henificado + 25% + Machos T2 Maní forrajero henificado + 35% + Machos T3 Maní forrajero henificado + 45% + Machos T4 Maní forrajero henificado + 55% + Machos T5 Maní forrajero henificado + 25% + Hembras T6 Maní forrajero henificado + 35% + Hembras T7 Maní forrajero henificado + 45% + Hembras T8 Maní forrajero henificado + 55% + Hembras T9 Leucaena henificada + 25% + Machos T10 Leucaena henificada + 35% + Machos T11 Leucaena henificada + 45% + Machos T12 Leucaena henificada + 55% + Machos T13 Leucaena henificada + 25% + Hembras T14 Leucaena henificada + 35% + Hembras T15 Leucaena henificada + 45% + Hembras T16 Leucaena henificada + 55% + Hembras The initial weight recorded for the factors and processes (interactions) than were treatments T14, T16, T15 yT8 with 633.03 g., 633.17 gr., 633.20 and 640.93 gr. respectively. In the variable gain weight every ten days, were higher in females and all assessments which averages at 21, 31, 41, 51 and 61 days were: 165.02, 206.28, 275.04, 330.05 and 398.8 grams respectively. While the treatments with average 13: 175.2, 219, 350.4 and 423.4 and treatment with averages of 15: 175.1, 218.8, 291.7, 350.1 and statistically exceeded 423 the rest. Feed intake was higher in the factor A Leucaena leucocephala with 560.43, 773.93, 1120.9, 1254.3 and 1627.9 grams, factor B concentration exceeded 55% in all other evaluations with: 563.33; 777.94; 1126.7; 1260.8 and 1636.4 grams respectively, while for the factor C females were also higher with averages of: 597.57; 825.21; 1195 , 1, 1337.4 and 1735.8 grams respectively, treatment with 6: 643.67, 888.9, 1287.4, 1440.6 and 1869.8 grams respectively, treatment with 13: 620.97; 857 , 5, 1241.9, 1389.8 and 1803.7 grams correspondingly, the treatment 15 with 638.37, 881.55, 1276.7, 1428.7 and 1854.3 grams appropriately and treating 16 with 622.25 , 859.28, 1244.5, 1392.6 and 1807.5 grams respectively. Feed conversion in the concentration of 55% achieved the highest average, 4.6, T4 treatment was higher with an average of 5.3, the performance of the channel did not show statistical differences. The highest benefit cost ratio of treatments were T3, T8 and T11con values of 1.84, 1.86 and 1.86 respectively currencies. Continue to research assessment more time to validate the results of this research and to deliver information to producers well proven in the field, the results at larger commercial leucaena leucocephala use as fodder for feeding rabbits supplemented with Try balanced treatments T3, T8 and T11 at the commercial level and deliver them to the producers with a technology package according to the present situation.